TOURISM MANAGEMENT OF NAGARI TUO PARIANGAN IN PARIANGAN TOURISM VILLAGE AREA, TANAH DATAR REGENCY - Nadila Sukma Sari; Geovani Meiwanda (FISIP Universitas Malikussaleh, 2022)
This research is based on the Tourism Management of Nagari Tuo Pariangan in the Pariangan Tourism Village Area, Tanah Datar Regency. The management of the Nagari Tuo Pariangan tourist village is carried out by the Nagari Tuo Pariangan Tourism Awareness Group. The purpose of this study was to describe the management of Pariangan Tourism Village. This research method is a qualitative method with a descriptive qualitative approach that describes the management process of the Nagari Tuo Pariangan tourist village. In addition, to find out the supporting factors in the management of the Nagari Tuo Pariangan tourist village. The results showed that the management in the Nagari Tuo Pariangan Tourism Village went through 4 stages, namely the planning stage, the organizing stage, the mobilization stage, and the supervision stage. The management of the Nagari Tuo Pariangan Tourism Village can be said to be not optimal because from the planning stage, Pokdarwis has implemented 14 work programs out of 18 work program plans. In the organization it must place skilled people in their fields so that the implementation of tourism management in the Nagari Tuo Pariangan tourist village is carried out properly. The supervision process in the management of the Nagari Tuo Pariangan tourist village is carried out by Pokdarwis, the Tourism Office and the Nagari Wali. Factors that support the management of the Nagari Tuo Pariangan tourist village are community participation factors; community economic impact; and promotion of nagari tuo pariangan.Penelitian ini didasarkan pada Pengelolaan Wisata Nagari Tuo Pariangan di Kawasan Desa Wisata Pariangan Kabupaten Tanah Datar. Pengelolaan desa wisata Nagari Tuo Pariangan dilaksanakan oleh Kelompok Sadar Wisata Nagari Tuo Pariangan. Tujuan penelitian ini adalah untuk mendeskripsikan pengelolaan Desa Wisata Pariangan. Metode penelitian ini adalah metode kualitatif dengan pendekatan kualitatif deskriptif yang menggambarkan proses pengelolaan desa wisata Nagari Tuo Pariangan. Selain itu juga untuk mengetahui faktor pendukung dalam pengelolaan desa wisata Nagari Tuo Pariangan. Hasil penelitian menunjukkan bahwa pengelolaan di Desa Wisata Nagari Tuo Pariangan dilaksanakan oleh Kelompok Sadar Wisata Nagari Tuo Pariangan melalui 4 tahapan yaitu tahap perencanaan, tahap pengorganisasian, tahap penggerakan, dan tahap pengawasan. Pengelolaan Desa Wisata Nagari Tuo Pariangan dapat dikatakan belum optimal karena dari tahap perencanaan, pokdarwis telah melaksanakan 14 program kerja dari 18 perencanaan program kerja. Pada pengorganisasiannya harus menempatkan orang-orang yang terampil di bidang mereka agar pelaksanaan pengelolaan pariwisata desa wisata Nagari Tuo Pariangan dilakukan dengan baik. Proses pengawasan dalam pengelolaan desa wisata Nagari Tuo Pariangan dilakukan oleh Pokdarwis, Dinas Pariwisata dan Wali nagari. Faktor yang mendukung dalam pengelolaan desa wisata Nagari Tuo Pariangan yaitu faktor partisispasi masyarakat; dampak ekonomi masyarakat; dan promosi nagari tuo pariangan.